Results of the introduction of ornamental peach cultivars from China and Japan - Komar-Tyomnaya Larisa (EDP Sciences, 2021)
The article presents the results of a nine-year study of 19 ornamental peach cultivars of Chinese and Japanese origin, introduced to the southern coast of Crimea. Cultivars with high ornamentality, degree and duration of flowering were identified. They are accession into early-medium, medium, mid-late, late and very late flowering groups. Their susceptibility to fungal diseases was determined.